Electrical and structural properties of camno-y ceramic compounds (2012)
By using the solid-state reaction method samples of Ca1-xYxMnO3 (CaMnO-Y) were prepared. Transport properties of the samples were studied from electrical resistivity ρ(T) and Seebeck coefficient S(T) measurements. The structural and morphological properties were researched by X-ray diffraction analysis and scanning electron microscopy (SEM), respectively. The Seebeck coefficient is negative throughout the studied temperature range indicating a conduction given by negative charge carriers. The magnitude of S(T) decreases with the yttrium level, which suggest an increase in the charge carrier density. The temperature behavior of electrical resistivity exhibit a semiconducting character; the magnitude of ρ(T) decreases with yttrium level reaching minimum values close to 0.5 Ω·cm. From the electrical resistivity and Seebeck coefficient experimental data it was possible to calculate the thermoelectric power factor, which shows maximum values around 0.12μW/K2cm.